Pengaruh Kualitas Pelayanan, Persepsi Harga, Cita Rasa Terhadap Kepuasan Konsumen (Studi Pada Rumah Makan Tok Patok) - Qari, Moh; Wahono, Budi; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to determine the influence of service quality, price perception and taste on consumer satisfaction (Study at the Tok Patok Restaurant). Sampling used a non-probability sampling method with a purposive sampling technique. A sample of 75 respondents was obtained. The data collection method uses a questionnaire. The data analysis technique used in this research is multiple linear regression. The research results show that simultaneously Service Quality, Price Perception and Taste have a positive and significant effect on Consumer Satisfaction. Likewise, partially Service Quality, Price Perception and Taste have a positive and significant effect on Consumer Satisfaction.  Keywords: Service Quality, Price Perception, Taste, Consumer Satisfaction